Five-Year Profiles of Prostate Cancer Patients in A Tertiary Hospital in Indonesia - Safriadi, Ferry; Novesar, Aidil Rahman (Majalah Kedokteran Bandung, 2021)
Prostate cancer is a malignant disease of the urogenital system, which is the second most common cancer in men and one of the leading causes of death in male population. In Bandung City, Indonesia, no data are available regarding the profile of prostate cancer patients. This study aimed to determine the profile of prostate cancer patients treated at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, which is the tertiary hospital in the most populated province in Indonesia, during the period of 2015-2019. This was a a retrospective descriptive study on secondary data from medical records. Results showed that most prostate carcinoma patients were was 67.95 ± 8.946 years old with most of them (n=92, 81.4%) had a history of hypertension and 62 patients (54.9%) did not have any history of smoking. Most patients had 20-40 cc prostate volume with hard consistency and without nodules; a PSA level of > 20 ng/ml; and a gleason score of 8-10 or poorly differentitated. Age affected increased incidence of prostate carcinoma with the highes prostate volume (20-40cc). The average PSA was 504.66 ± 10.26 and the median gleason score was 8 (6-10). The highest prostate volume is 20-40cc with hard consistency without nodule and the highest PSA value is > 20 ng/ml with a Gleason score of 8-10, showing a poorly differentiated condition.